2020
DOI: 10.3390/s20185316
|View full text |Cite
|
Sign up to set email alerts
|

User-Experience with Haptic Feedback Technologies and Text Input in Interactive Multimedia Devices

Abstract: Remote control devices are commonly used for interaction with multimedia equipment and applications (e.g., smart TVs, gaming, etc.). To improve conventional keypad-based technologies, haptic feedback and user input capabilities are being developed for enhancing the UX and providing advanced functionalities in remote control devices. Although the sensation provided by haptic feedback is similar to mechanical push buttons, the former offers much greater flexibility, due to the possibility of dynamically choosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, haptic studies on touch screens have mainly focused on modeling the click vibrations that occur at moments of state transition of a button rather than on basic perceptual characteristics [31]. Since Fukumoto and Sugimura [32] first introduced the "active touch(click)" concept, studies have been conducted on the magnitude, duration, and stimulator for vibration signals to implement a significantly realistic haptic feedback of the press-and-release stroke of a virtual button on a touch screen [33][34][35][36][37][38]. These studies have important implications because pressing a button is preferred over using touch screens in vehicles, where visual distraction can be a problem.…”
Section: Related Workmentioning
confidence: 99%
“…However, haptic studies on touch screens have mainly focused on modeling the click vibrations that occur at moments of state transition of a button rather than on basic perceptual characteristics [31]. Since Fukumoto and Sugimura [32] first introduced the "active touch(click)" concept, studies have been conducted on the magnitude, duration, and stimulator for vibration signals to implement a significantly realistic haptic feedback of the press-and-release stroke of a virtual button on a touch screen [33][34][35][36][37][38]. These studies have important implications because pressing a button is preferred over using touch screens in vehicles, where visual distraction can be a problem.…”
Section: Related Workmentioning
confidence: 99%
“…ERM and LRA actuators are commonly applied for the same purposes [6,7], mainly used in smartphones. From study [8], it was concluded that LRA actuators are much more battery efficient than ERM actuators. Piezo actuators have also been recently embedded on the new Windows 11 trackpads, according to Boréas Technologies [9].…”
Section: Introductionmentioning
confidence: 99%
“…In [ 2 ], the problem of remote control devices commonly used for interaction with multimedia equipment and applications (smart TVs, gaming, etc.) was addressed.…”
mentioning
confidence: 99%